2020
DOI: 10.21037/atm-20-2990
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib as first-line treatment in patients with advanced hepatocellular carcinoma: a phase II clinical trial

Abstract: Background:The prognosis for advanced hepatocellular carcinoma (HCC) remains clinically unsatisfying.Apatinib has proven to be a very effective treatment for advanced HCC in our previous retrospective study.Our aim in this study was to evaluate the efficacy, safety, and toxicity of apatinib in patients with advanced HCC.Methods: This single-arm, open-label phase II clinical trial enrolled patients with advanced HCC. These patients received apatinib, 500 mg once daily, until disease progression, unacceptable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This is the case of donafenib (targeting RAF and VEGFR) (NCT02645981) 69 and apatinib (targeting VEGFR-2) (NCT02329860 and NCT03046979). 70 The efficacy of a sequential therapy based on TKIs is also being evaluated. A recent study has demonstrated that lenvatinib is a good option as a third-line therapy for those patients progressing under treatments with sorafenib and regorafenib.…”
Section: Therapies Under Studymentioning
confidence: 99%
“…This is the case of donafenib (targeting RAF and VEGFR) (NCT02645981) 69 and apatinib (targeting VEGFR-2) (NCT02329860 and NCT03046979). 70 The efficacy of a sequential therapy based on TKIs is also being evaluated. A recent study has demonstrated that lenvatinib is a good option as a third-line therapy for those patients progressing under treatments with sorafenib and regorafenib.…”
Section: Therapies Under Studymentioning
confidence: 99%
“…In China, apatinib has been approved recently for the treatment of HCC due to its satisfactory efficiency. A randomized clinical trial showed that apatinib prolongs the OS of BCLC stage B or C HCC patients, which has also been validated in several retrospective studies (17)(18)(19)(20). In addition, several researches indicated that apatinib is effective in advanced HCC patients with PVTT when combined with TACE (21,22).…”
Section: Introductionmentioning
confidence: 78%
“…Notably, in another phase II clinical trial, for intermediate and advanced hepatocellular carcinoma patients, the patients receiving apatinib as the first-line therapy exhibited a tremendous potential in the long-term curative effect (mPFS: 8.7 months; mOS:13.8 months) ( 47 ). Therefore, we intend to conduct a new prospective study to fill the gap that there is a limited related theoretical basis for the therapeutic efficacy of apatinib in the first-line treatment of recurrent or metastatic advanced cholangiocarcinoma in the future.…”
Section: Discussionmentioning
confidence: 99%